An ex-situ approach for cultivating coralline algae in a restoration perspective - A. Puccini; S. Kaleb; G. Ceccherelli; D. Porrelli; P. Stipcich; A. Falace (Marine Biology, 2025)
Mediterranean coralligenous reefs are hotspots of biodiversity, but they are declining due to multiple impacts, prompting a growing number of conservation and restoration efforts. Restoration through the outplanting of the habitat foundation species, crustose coralline algae (CCA, Rhodophyta, Corallinophycidae), is still largely unexplored, although they make a major contribution to building these valuable ecosystems. In this study, we tested the feasibility of ex-situ culture of Lithophyllum stictiforme , one of the most common CCA of the coralligenous reefs, with nutrient-enriched artificial seawater medium, contributing to the knowledge of early life stage development and calcification. Thalli fragments with conceptacles were collected at a depth of 28 m (Costa Paradiso, northern Sardinia). We tested two light intensities, (L − 40 µmol photons m −2 s − 1, L + 160 µmol photons m −2 s −1 ) and two temperatures, (T − 14 °C, T + 20 °C), the lower settings were chosen to simulate conditions at the sampling site, while the higher values were explored as potential growth promoters. Spore settlement, density and growth were estimated for two-weeks. Calcification was analyzed at the end of the culture period using Scanning Electron Microscopy in combination with Energy Dispersive Spectroscopy (SEM-EDS). The L − treatments had a positive effect on germination success and density, whereby the growth of the germination disc was enhanced in the L − T + treatment. SEM-EDS showed that the marginal area of the germination discs had a higher Ca content than the core area, and that the L − treatments promoted a higher cell wall Ca percentage.

Towards a sustainable fisher-dolphin coexistence: Understanding depredation, assessing economic damage and evaluating management options - G. La Manna; N. Arrostuto; M. Moro Merella; P. Stipcich; N. Fois; G. Sarà; G. Ceccherelli (Journal of Environmental Management, 2024)

Determinants of group size in the common bottlenose dolphins: the role of water temperature and noise - G. La Manna; F. Ronchetti; F. Perretti; G. Ceccherelli (Behavioral Ecology and Sociobiology, 2023)

Alpha and beta diversity in Mediterranean macroalgal assemblages: relevancy and type of effect of anthropogenic stressors vs natural variability - L. Piazzi; G. Ceccherelli (Marine Biology, 2020)

The invasion of Caulerpa cylindracea in the Mediterranean: the known, the unknown and the knowable - L. Piazzi; D. Balata; F. Bulleri; P. Gennaro; G. Ceccherelli (Marine Biology, 2016)

Human trampling effects on Mediterranean coastal dune plants - E. Farris; S. Pisanu; G. Ceccherelli; R. Filigheddu (Plant Biosystems, 2013)

Human impact on Paracentrotus lividus: the result of harvest restrictions and accessibility of locations - G. Ceccherelli; A. Pais; S. Pinna; N. Sechi; L. A. Chessa (Marine Biology, 2011)

The inactive temporary component: an unexplored fraction of meiobenthos - A. C. Pati; G. Belmonte; V. U. Ceccherelli; F. Boero (Marine Biology, 1999)